2021
DOI: 10.3389/fceng.2021.742322
|View full text |Cite
|
Sign up to set email alerts
|

Silver Nanoparticle Synthesis Using an Inkjet Mixing System

Abstract: Individual nanoscale silver particles were produced using an inkjet mixing system. First, the behaviors of colliding droplets were investigated to prepare to conduct the synthesis without splitting merged droplets. When small droplets collided, they merged to form droplets that stayed in a state of coalescence at a higher discharging velocity. In addition, by changing the orientation at the collision point, the droplet velocity could be increased. Then, silver nanoparticle synthesis was conducted under conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…It obviously indicates that the faster mixing in the FNP facilitates rapid nucleation and homogeneous precipitation. 26 Moreover, the P-NPs prepared from P(St-MA) at a concentration of 7 mg mL −1 in a turbulent jet flow mode showed an average size of 141 nm, respectively, whereas the P-NPs obtained from P(MMA-MAA) under the same conditions were measured at 197 nm.…”
Section: Resultsmentioning
confidence: 98%
“…It obviously indicates that the faster mixing in the FNP facilitates rapid nucleation and homogeneous precipitation. 26 Moreover, the P-NPs prepared from P(St-MA) at a concentration of 7 mg mL −1 in a turbulent jet flow mode showed an average size of 141 nm, respectively, whereas the P-NPs obtained from P(MMA-MAA) under the same conditions were measured at 197 nm.…”
Section: Resultsmentioning
confidence: 98%
“…Our previous study confirmed that by increasing B , the once merged droplets were prevented from splitting apart over a wider range of u . This, therefore, resulted in a wider range of We and increased the mixing performance in the merged droplets normalW normale = ρ d 1 u 2 σ B = b d 2 …”
Section: Methodsmentioning
confidence: 99%
“…This, therefore, resulted in a wider range of We and increased the mixing performance in the merged droplets. 24 = d u We (1)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, there are many reports on device development, including reactors, mixers, and pumps [1][2][3][4]. There are also a wide variety of reports on reaction operations [5,6], especially mixing, that take advantage of the tiny mixing space in micro-devices and the resulting short diffusion distance [7]. However, most of these reports focus on separation and specifically on extraction [8][9][10].…”
Section: Introductionmentioning
confidence: 99%